Association of amniotic fluid sludge with preterm labor and histologic chorioamnionitis in pregnant Japanese women with intact membranes: A retrospective study. Issue 1 (8th October 2019) - Yasuda, Shun; Tanaka, Masayo; Kyozuka, Hyo; Suzuki, Satoshi; Yamaguchi, Akiko; Nomura, Yasuhisa; Fujimori, Keiya
Abstract: Aim: The presence of amniotic fluid sludge has been identified as a risk factor for preterm birth. We sought to validate the clinical characteristics of amniotic fluid sludge in Japanese pregnant women with preterm labor and intact membranes. Methods: This was a retrospective study of 54 patients. The presence of amniotic fluid sludge was confirmed using transvaginal ultrasonography data during pregnancy. The following data were collected: gestational age, the presence of histologic chorioamnionitis, time from the diagnosis of threatened premature labor to delivery, oncofetal fibronectin (onfFN) levels, C‐reactive protein peak value levels, cervical length at the time of onset of threatened premature labor and types of neonatal complications. Results: Significant differences ( P = 0.03) were observed in the age at delivery in relation to the presence of amniotic sludge: delivery occurred at 28.3 ± 4.5 weeks and 31.7 ± 4.3 weeks in sludge positive patients and sludge‐negative patients, respectively. Presence of sludge in patients diagnosed with histological chorioamnionitis at <37 weeks of gestation differed significantly ( P = 0.01): sludge‐positive, 81.8%; sludge‐negative, 20.9%. Among the sludge‐positive patients, 100% were positive for serum onfFN (≥50 ng/mL), whereas only 54% of sludge‐negative patients were positive for serum onfFN ( P = 0.03). Presence of amniotic fluid sludge did not significantly affect neonatal complications. Conclusion: Our results confirmed previous findings that amniotic fluid sludge is a self‐determining risk factor for preterm birth and chorioamnionitis in pregnant Japanese women.